2006
DOI: 10.1016/j.brainres.2006.09.055
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age on the response to fibroblast growth factor-2 treatment in a rat model of stroke

Abstract: Basic fibroblast growth factor (FGF-2) has been reported to protect against ischemic injury in the brains of young adult rodents. However, little is known about whether FGF-2 retains this capability in the aged ischemic brain. Since stroke in human is much more common in older people than among younger adults, to address this question is clinically important. In this study, aged (24-month-old) rats were treated with intracerebroventricular infusion of FGF-2 or vehicle for 3 days, beginning 48 hr before (pre-is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 25 publications
0
29
0
Order By: Relevance
“…The few studies available in literature have shown varying results in the histological outcomes in young vs. aged animal 4, 6, 1923 . There have been reports of increased 22, 24 , equal 23, 25 or decreased infarct volumes 4, 1921 in aged vs. young animals. The discrepancies may be due to the difference in animal strains, animal sexes, or ischemic models used in the studies.…”
Section: Discussionmentioning
confidence: 99%
“…The few studies available in literature have shown varying results in the histological outcomes in young vs. aged animal 4, 6, 1923 . There have been reports of increased 22, 24 , equal 23, 25 or decreased infarct volumes 4, 1921 in aged vs. young animals. The discrepancies may be due to the difference in animal strains, animal sexes, or ischemic models used in the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Male Sprague-Dawley rats weighing 280-310 g were anesthetized with 4% isoflurane in 70% N 2 O/30% O 2 using a mask. Permanent distal middle cerebral arterial (MCA) occlusion (MCAO) was performed as described previously (Nawashiro et al, 1997; Won et al, 2006). A 2-cm incision was made between the right orbit and tragus under the surgical microscope.…”
Section: Methodsmentioning
confidence: 99%
“…Focal ischemia was performed as previously described [28]. Briefly, immediately thereafter, both common carotid arteries (CCAs) were occluded with microclips and rats underwent simultaneous occlusion of the middle cerebral artery (MCA) and both CCAs for 60 min.…”
Section: Transient Focal Cerebral Ischemiamentioning
confidence: 99%